Math CentralQuandaries & Queries


Question from Erick, a teacher:

please explain to me how to convert an equation from the form y=mx+c to Ax+By+C=0 form.

Hi Erick,

With the equation $y = mx + c$ I would first add $-y$ to both sides. This gives $mx - y + c = 0$ which may be all you need as it is in the form $Ax + BY + C = 0$ with $A = m, B = -1$ and $C = c.$

If either of the constants $m$ or $c$ is a fraction you can multiply both sides of $mx - y + c = 0$ by the denominators of the fractions and simplify to obtain the form $Ax + By + C = 0$ with all the coefficients integers.


About Math Central


Math Central is supported by the University of Regina and the Imperial Oil Foundation.
Quandaries & Queries page Home page University of Regina